A systematic scoping review reveals that geographic and taxonomic patterns influence the scientific and societal interest in urban soil microbial diversity - Simon Masson; Matteo Chialva; Davide Bongiovanni; Martino Adamo; Irene Stefanini; Luisa Lanfranco (Environmental Microbiome)
Abstract Urban green areas provide multiple ecosystem services in cities, mitigating environmental risks and providing a healthier environment for humans. Even if urban ecology has become popular in the last decade, the soil environment with its microbiota, which sustains many other biodiversity layers, remains overlooked. Here, a comprehensive database of scientific papers published in the last 30 years investigating different aspects of soil microbial diversity was built and systematically reviewed. The aim was to identify the taxa, experimental methods and geographical areas that have been investigated, and to highlight gaps in knowledge and research prospects. Our results show that current knowledge on urban soil microbiota remains incomplete, mainly due to the lack of publications on functional aspects, and is biased, in terms of investigated taxa, with most studies focused on Prokaryotes, and geographic representativeness, with the interest focused on a few large cities in the Northern hemisphere. By coupling bibliometrics with statistical modelling we found that soil microbial traits such as biomass and respiration and omics techniques attract the interest of the scientific community while multi-taxa and time-course studies appeal more to the general public.